Future positive : change your mindset for a positive future - De Bono, Edward (London : Vermilion, 2017)
If we make a deliberate and positive effort to change our thinking we can secure a positive future, and we can harness the focused power of human thinking by releasing it from its pettiness.
Includes index.
Keywords: Positive psychology; Self-actualization (Psychology).; Self-realization.